Introductory Experiential Learning in IPE Teams: Changes in Team Collaboration and Cultural Attitudes and Beliefs - Farris, Karen B.; Bavireddy, Vinoothana; Bishop, Thomas; Marshall, Vincent D.; Anderson, Olivia (Journal of Research in Interprofessional Practice and Education, 2023)
Background: An introductory, longitudinal, authentic experiential IPE opportunity named LIFE was delivered. The objectives were to 1) compare attitudes, including cultural attitudes and beliefs, and team behaviours of learners over time, and 2) assess association between participation in LIFE and changes in team attitudes and performance. Methods: Students (n = 48) from eight schools worked in eight teams. Each team was assigned to a patient/family, who was asked about health and healthcare experiences. Students completed Students’ Perceptions of Interprofessional Clinical Education–Revision 2 (SPICE-R2), Cultural Attitude and Belief Scale (CABS), and Interprofessional Collaborator Assessment Rubric (ICAR). Analyses focused on differences over time for all participants and by team. Findings: Knowledge of roles improved for four teams, and five teams showed improvements in “techniques” to interact with diverse patients. Notably, “communication,” “collaborative working,” and “roles” changed across three teams for ICAR. One team showed improvements in all three assessments and two teams showed little to no changes. Conclusion: LIFE was associated with improvements in “roles” and “techniques” to help teams interact with diverse patients.